The influence of TNF alpha -308 G/A polymorphism on oxidative stress in patients with chronic lymphocytic leukemia. (March 2017) - Jevtovic-Stoimenov, T.; Cvetkovic, T.; Despotovic, M.; Basic, J.; Cvetkovic, J.; Marjanovic, G.; Pavlovic, D.
Abstract: The aim of this study was to examine the association of TNF-α-308G/A polymorphism with CLL and influence on oxidative stress parameters.Significant difference in the genotype and allele distribution was obtained in TNFA subgroup of patients.Significantly higher GPx activity and TBARS and lower catalase activity were detected in CLL.Significantly higher catalase and lower GPx activities were detected in PBMC of TNFG compared to TNFA subgroup, while TBARS were higher in TNFA.Oxidative stress in CLL patients highly correlates with the presence of TNFA subgroup. Increased TBARS, GPx and decreased catalase activity are associated with TNF-α-308A allele containing genotypes.